Usability as a Premise of Quality: First Steps Towards the Validation of the System Usability Scale (SUS) into Spanish - Tor-Carroggio, Irene; Segura, Daniel; Soler-Vilageliu, Olga (Journal of Audiovisual Translation, 2019)
Usability is a key factor when talking about the quality of a product. The System Usability Scale (SUS) is one of the most popular tools to measure usability due to its numerous advantages and, therefore, a very useful quality assessment tool. Originally designed in English, it is available in some other languages, such as Persian and Greek but no validated version in Spanish can be found yet. This paper bridges this gap by describing the process of statistically validating the SUS into Spanish. The results show that our translation of the SUS is reliable, although our modest sample of informants (N = 50) leaves room for improvement and future research. The validation of the SUS is framed within a European project that will use it for its testing phase.